UNIVERSITY TEACHING AS A FORMATIVE PRACTICE: RATIONALITIES, TENSIONS, AND IMPLICATIONS FOR INITIAL TEACHER TRAINING - Barbosa, Ronaldo dos Santos; Araújo, Maria do Rosário Sá (Seven Editora, 2026)
This article examines the predominant rationalities in university teaching and their impacts on the initial training of teachers, with emphasis on undergraduate teacher education programs in Brazil. It argues that conceiving teaching as mere content transmission, sustained by a technical-instrumental rationality, weakens the pedagogical and reflective dimension essential to the education of future educators. The study, of a theoretical-reflective nature, is based on a critical narrative review of the literature on higher education teaching, drawing on Habermas’s concept of rationality (1982, 1987) and contributions from scholars in university pedagogy. The central aim is to discuss the tension between technical-instrumental and pedagogical rationalities, identifying their manifestations in teaching practices and their implications for teacher education. The analysis indicates that the predominance of the technical-instrumental model perpetuates transmission-centered practices, undermining the development of pedagogical competencies among prospective teachers. It concludes that overcoming this instrumental perspective requires institutional recognition of the pedagogical dimension and investment in the continuing education of university professors. Such measures are crucial to foster more reflective, intersubjective, and socially committed teaching practices, thereby strengthening the quality of basic education. DOI: https://doi.org/10.56238/sevened2026.008-098